Should Banking Be Kept Separate from Commerce - Alexander Raskovich (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2008)
In the U.S., unlike much of the rest of the world, the mixing of banking and commerce is largely prohibited. One exception is industrial loan companies (ILCs), state chartered depository institutions some of which are owned by commercial parents. In 2006, the FDIC put a moratorium on the chartering of new ILCs pending resolution of a controversy sparked by Wal-Mart's application to start up an ILC in Utah. Wal-Mart subsequently withdrew its bid. This paper reviews the major arguments that have been raised against the mixing of banking and commerce, finding most to be theoretically weak or lacking in empirical support, and discusses several efficiencies that may arise from the integration of banking and commerce.
Keywords: G21; G28; L40; K21; K23; 330; Regulation; Industrial Loan Companies; Banking; Antitrust